Mitochondrial DNA New Insights - Seligmann, Hervé (IntechOpen, 2018)
The very short genomes of mitochondria summarize the complexity of molecular biology and its interactions with cellular and whole organism biology. Studies of mitogenomes contribute to the understanding of molecular biology and evolution, and to health management. Despite or even due to their small sizes, mitogenomes continue to surprise us. Studies of mitogenomes reveal the details of molecular organization and its evolution under constraints for miniaturization.